"Features of Far North Life Pictured by the Bartlett-Academy of Natural Sciences Greenland Expedition" (Philadelphia Evening Bulletin, 1930)
"With lace-top boots and hair nicely sleeked down with walrus oil, these young Eskimo belles help make the northern lights seem brighter. They nonchalantly puffed their cigarettes visiting the chief engineer of the expedition ship, the Morrissey." With clipping